Neutrophil/lymphocyte ratio as serum inflammatory biomarker in patients with moderate-to-severe plaque psoriasis - Maria E. Agapito-Valgas; Lara J. Justo-Silva; Fraciele Cascaes da Silva; Fabiana Oenning-; Gustavo M. Amorim; Sueli Carneiro (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Introduction: Psoriasis is an immune-mediated, chronic, inflammatory, systemic disease that primarily affects the skin and joints. Despite advances in the comprehension of the disease, there is still a lack of biomarkers available for clinical use. Objective: To evaluate neutrophil-lymphocyte ratio (NLR) as a marker of systemic inflammatory status in patients with moderate to severe plaque psoriasis vulgaris, compared with controls. Methods: Observational case-control study, conducted in a public hospital unit, focused on skin disease. A total of 165 patients with psoriasis and 187 healthy subjects seen between August and December 2020 were studied. Results: The group of cases showed a greater median of NLR compared with controls (medium = 1.96, p = 0.032). When stratified by age, the median NLR was higher in individuals between 31 and 60 years, with statistical significance. No differences were identified in gender, presence of arthritis or comorbidities. Study limitations: Observational, retrospective, single-center study based on medical records review. Conclusion: NLR was higher in individuals with psoriasis when compared with controls. It is simple, inexpensive and available in all levels of care, based on an elementary laboratory test that is already part of the routine care of patients with psoriasis. Its use in evaluating systemic inflammation could contribute to better management of psoriatic disease.